Victorien

answers: 1

Register to add an answer

Answer:

taking my first course in Probability and one of my homework problems is to prove that for any two sets:

P(A∪B)=P(A)+P(B)−P(A∩B)

Note that the function P is the probability of an event happening. From the third axiom, we are given that for any two disjoint sets, that is A∩B=∅:

P(A∪B)=P(A)+P(B)

My thought process follows from this third axiom, but I run into a problem near the end:

Since A and B are disjoint sets, P(A)=P(A−B) and P(B)=P(B−A), so

P(A∪B)=P(A)+P(B)=P(A−B)+P(B−A)

From this, it appears that we are essentially taking the symmetric difference of A and B. This, to me, seems to be equivalent to:

P(A−B)+P(B−A)=P(A)+P(B)−P(A∩B)

Hence, by my logic:

P(A∪B)=P(A)+P(B)−P(A∩B)

Which, in essence, doesn't care whether two sets are disjoint or not as we are subtracting the intersection of them. If the sets are disjoint, then the intersection is merely null. If they intersect, then we are removing the "extra pieces".

you can solve your problem by using this solution

184

Boris

For answers need to register.

203

cents

The time for answering the question is over

Contacts

mail@expertinstudy.com

Feedback

Expert in study

About us

For new users

For new experts

Terms and Conditions